Connecting the cytotoxic and genotoxic effects of multi-walled carbon nanotubes to their physicochemical properties - Louro, Henriqueta (2017)
Poster abstract publicado em: J Clin Toxicol 2017, 7:3 (suppl):67. doi: 10.4172/2161-0495-C1-024-005